Implementation of School-Based Management (SBM) in Supporting the Strengthening of Islamic Character Education at Al-Firdausy Middle School - Nisak, Alfatun (Universitas PGRI Sumatera Barat, 2025)
Islamic character education is an important aspect in shaping students' personalities in the school environment. To support this, effective and contextual educational management is needed. This article aims to examine the implementation of School-Based Management (SBM) in strengthening Islamic character education at Al-Firdausy Middle School. The method used is a qualitative approach with a case study design. Data were obtained through observation, interviews, and documentation of Islamic programs run by the school. The results show that SBM provides flexibility for schools in designing and implementing religious programs, such as congregational Dhuha prayers, morning recitation of Surah Al-Waqi'ah, and local content learning in the form of yellow book studies. These programs have proven effective in fostering the values of religiosity, discipline, and responsibility in students. The implementation of SBM, which is participatory and focused on educational quality, has encouraged the formation of a school environment that supports the formation of Islamic character comprehensively and sustainably.